Study guides

☆☆

Q: How do you factor -9x3-3x2 plus 3x plus 1?

Write your answer...

Submit

Still have questions?

Related questions

(-3x - 1)(3x - 7)

3x(2y + 1)

9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2

3x and x^2 - 3x + 1

(3x + 1)(x + 5)

(x + 5)(3x + 1)

3(x2 + 3x + 1)

3x(56x2-15x+1)

3x2 + x = x*(3x + 1)

(2x + 1)(3x - 1)(3x - 1)

3x(2x + 1)

(x + 2)(3x - 1)(3x + 1)

(3x - 7)(x - 1)(x + 1)

168x3 - 45x2 + 3x = 3x(56x2 - 15x + 1) = 3x(7x - 1)(8x - 1)

(-3x+1)(-2x+1)

(3x - 1)(x + 2)

(x - 1)(3x + 5)

-((4x + 1)(x - 1))

(x + 1)(3x + 10)

3x2 + 10x + 3 = (x + 3)(3x + 1).

(x + 1)(3x + 5)

No. You'd have to use the ABC-formula

(x + 2)(x + 1)

You notice the first two items, 3bx + 3x factorizes into 3x(b+1). And the last two, by +y factorize into y(b+1) . So (b+1) is a common factor, so you can factorize these two into (b+1)(3x+y)

(3x - y)(3x - 5y) and (2x + 1)(2x + 11)